Social justice in development studies literature Historical concept analysis - Abdelhameed, Ingy Mohamed (European Journal of Sustainable Development, 2016)
This paper critically analyses the importance of social justice in development studies. In doing so, it raises some questions about the attention that has been given to social justice in development literature since late Forties, especially, How did this affect development policies on both national and international levels? And How all above mentioned were affected by the great international events in more than sixties years? It uses historical conceptual analysis to explore the main changes that social justice as a concept has gone through in development studies and the impact of ideological and political changes on it.